STUDI PEMBUATAN SCAFFOLD BOVINE HYDROXYAPATITE DARI TULANG SAPI UNTUK APLIKASI IMPLAN TULANG MANDIBULA MENGGUNAKAN METODE KALSINASI - Solechan -; Saifudin Alie Anwar (Universitas Muhammadiyah Semarang, 2014)
Waste cow bone bakso balungan in Central Java own produces 31.9 tons/day of merchants bakso. Bovine bone hydroxyapatite material can be made bioceramik derivative products to repair damaged hard tissues of the body due to brittle bones, bone cancer or accidents. Tissue damage including bone tumors. Tumors of the mandibular potentially cause interference and need removal of mandibular tumors that cause cracks.It is necessary for the formation of mandibular reconstruction of mandibular continuity with transplantation scaffolds. The use of limited donor transplanstasi, whereas synthetic implant material is very expensive. Preparation of bovine hydroxyapatite scaffold waste cow bone bakso balungan of reinforced PCL with calcination method would be lesscostly. The process of manufacture of bovine bone hydroxyapatite by cutting waste kanselosa in size 10 mm x 10 mmx 10 mm, and then calcined at 300, 6000, 900, and 1200 oC for 2 hours. Furthermore PCL scaffold is reinforced with a concentration of 1, 3, and 5%. by means of dip coating for several minutes. Bovine hydroxyapatite scaffold tested showed an increase XRD diffractogram with the calcination temperature gavesharp peaks with high intensity high crystal or crystalline form perfect but with the addition of PCL deficient diffraction process with a decrease inttensitas. The pore size and porosity influenced the high calcination but lower compressive strength. With the addition of the PCL layer increases the compressive strength, but decrease the pore diameter and porosity that is still under scaffolds characteristics and mechanical properties of commercial.